Validation study of three-dimensional scanning of footwear impressions. Issue 1 (2nd January 2022) - Montgomerie, Casey; Raneri, Domenic; Maynard, Philip
ABSTRACT: Three-dimensional impressions are typically photographed and cast for further comparison when reference items become available to investigators. Three-dimensional scanning has been proposed as a more time-efficient and objective, less destructive method for footwear impression analysis. This project sought to acquire repeat scans of outsole footwear impressions and corresponding shoes at high resolutions to investigate the precision and accuracy of 3D scanning on footwear and impressions. Impressions were created using three footwear types representative of footwear encountered in casework. Scans of impressions were created using the Artec Spider structured-light scanner. Calculations of the statistical variability between scans were carried out using the CloudCompare software package. The distance between corresponding points within the impression tested for precision (n = 6) averaged 0.45 mm, σ 0.29 mm. When comparing the impression to the reference shoe, the distance between corresponding points averaged 2.41 mm, σ 1.98 mm. The maximal differences within the scans were at the toe of the shoe and may be due to flexion, as well as damage to the soil around the edges of the impression. This research has validated the hardware and software used to acquire data from a 3D impression and from the reference item that produced the trace.